Trilingual comic development (madurese- indonesian-english) science adventure in anjhir hill as an innovation in introduction of natural tourism in elementary school students - Fijriyah, Izzah (Universitas Nusantara PGRI Kediri, 2023)
Anjhir Hill is a natural tourist attraction located in Tragah District, Bangkalan Regency which is still new and is still rarely known by many people. Based on observations, these problems are caused by a lack of promotion and publication to the wider community. Therefore, there is a need for promotional innovations to introduce this tourist destination. The purpose of developing this comic in three languages ​​is an effort to promote the natural tourist spot of Anjhir hill through language and science approaches. This research is development research using 4D development model which has 4 stages, they are Define, Design, Development, and Dissemination. The subjects of this study were high grade elementary school students in three elementary schools in Madura. Data collection techniques were carried out by observation, interviews, and questionnaires. Based on the percentage validation results from tourism promotion experts, linguists, and materials experts, it was obtained that they were 90%, 85%, and 80.5%, respectively. So that it is known that from the results of expert validation, comics developed obtain a valid category. In addition, based on the results of student questionnaire with an interpretation of score based on the Linkert scale as a whole, a percentage value of 85% is obtained in the very good category.